Islam Populer sebagai Pencarian Identitas Muslim Kelas Menengah Indonesia - Wasisto Raharjo Jati (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
This article aims to analyze the construction of identity in the case study of Middle-Class Muslim in Indonesia. The term “Popular Islam” is part of an academic term to make Islam an identity for the Middle-Class Muslim in Indonesia. This term can be interpreted into two premises: popular Islam as a commoditization of Islamic value and Islam as part of the celebration of Islamic day. These terms later then forked between Islamization and indigenization, thus creating their assorted shades of Middle-Class Muslims in Indonesia. Consumption then presents a cultural sign to distinguish the Middle Class. It was later manifested in the mass cultural products on behalf of Islam. That image displayed on consuming the product and then create a construction of an Islamic Middle Class, religious Middle Class, and the Arabized Middle Class. This paper will elaborate more deeply about searching for identity and its impact on Middle-Class Muslims in Indonesia.